Species diversity and abundance of Staphylinidae beetles in monoculture and polyculture vegetable agroecosystems in Cikole Village, West Bandung District, Indonesia - LINDUNG TRI PUSPASARI; AMEILIA ZULIYANTI SIREGAR; SUPUTA SUPUTA; ABDUL HAFIZ AB MAJID (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Puspasari LT, Siregar AZ, Suputa, Majid AHA. 2025. Species diversity and abundance of Staphylinidae beetles in monoculture and polyculture vegetable agroecosystems in Cikole Village, West Bandung District, Indonesia. Biodiversitas 26: 2139-2147. Biodiversity plays an important role in maintaining ecosystem balance and supporting the sustainability of agricultural systems. One group of insects that contributes significantly to biological control is Staphylinidae (Coleoptera). Staphylinidae as biological control can be affected because monoculture practices can increase pest pressure, which is often overcome using synthetic pesticides. This study was conducted to fill this knowledge gap by measuring and comparing the diversity and abundance of Staphylinidae on tomato plants (Solanum lycopersicum) and chili (Capsicum annuum) in four types of vegetable agroecosystem habitats: monoculture tomatoes, polyculture tomatoes, monoculture chilies, and polyculture chilies. The study conducted in the Cikole Lembang area, West Bandung District, Indonesia from July to September 2024 using the descriptive-exploratory method showed that the highest diversity was found in the Chili Polyculture (CP) agroecosystem with a H': 1.655 value, while the lowest was in Tomatoes (T) with H': 1.103. The highest uniformity was recorded in the CP agroecosystem (E: 0.572), indicating a more even distribution of individuals among species. Monoculture agroecosystems such as T (E: 0.398) have an uneven distribution of individuals, reflecting the dominance of certain species. The highest dominance value in T (D: 0.584) indicates the presence of a strong dominant species. In contrast, CP shows the lowest dominance value (D: 0.345), indicating a more balanced and diverse community. The highest similarity was observed between Chili (C) and Tomato Polyculture (TP) (index 0.84), indicating similar Staphylinidae communities in monoculture chili and polyculture tomato planting patterns. Polyculture planting patterns provide benefits to the diversity of Staphylinidae communities, especially in creating habitats that support unique species and increasing the even distribution of species. Monoculture, although efficient in production, tends to favor the dominance of certain species, which can limit biodiversity and increase the risk of ecosystem imbalance.